PHYSICAL REPRESENTATION OF NATIONAL IDENTITY IN JULIAN BARNES’S NOVEL “ENGLAND, ENGLAND” (Revista Inclusiones, 2021)
The search for the national identity is a central theme in Julian Barnes’s England, England (1999).The article studies various aspects of the physical representation of the idea in the novel. On the onehand, the landscape in the novel is tightly connected with the historical and pseudo-historicalmeanings which make it an essential part of Barnes’s model of the national identity. On the otherhand, the novel recreates the process of physical reshaping of the national landscape as a metaphorfor reshaping the nation. The article proves that the three landscapes successively emerging in thethree parts of the novel are endowed with various degrees of symbolic meaning. The first part of thenovel presents the landscape of the childhood memories blended with the character’s emotionalreminiscences. The second part focuses on role the simulacrum landscape plays in the myth creationas the quintessence of Englishness is materialised in the replicas of historic and cultural sites in thetheme park. In the third par, Anglia’s landscape is shown as devoid of any historical meaning for theinhabitants of the island.